Critique of Metaphysics and critical Metaphysics - Pringe, Hernán (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
Kant´s critique of reason has the main goal of determining the possibility of Metaphysics as a science. The purpose of this paper is to provide an overview of the critical Metaphysics (i.e. the Metaphysics, the possibility of which is finally established by the critique of reason). We shall distinguish three kinds of metaphysical knowledge: the metaphysics of experience, the Metaphysics of Morals and the practical-dogmatic Metaphysics. We shall then discuss the way in which these Metaphysics make up a single system.
Keywords: critique; metaphysics; system